Noma and Necrotizing Fasciitis of the Face and Neck - Miller, Lauren E.; Shaye, David A. (Facial Plastic Surgery, 2021)
Necrotizing fasciitis (NF) is part of the class of necrotizing soft tissue infections characterized by rapid fascial spread and necrosis of the skin, subcutaneous tissue, and superficial fascia. If left untreated, NF can rapidly deteriorate into multiorgan shock and systemic failure. NF most commonly infects the trunk and lower extremities, although it can sometimes present in the head and neck region. This review provides an overview of NF as it relates specifically to the head and neck region, including its associated clinical features and options for treatment. Noma, a related but relatively unknown disease, is then described along with its relationship with severe poverty.
Keywords: noma; necrotizing fasciitis; reconstructive surgery